2020
DOI: 10.1038/s41598-020-69704-6
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation-induced bistability in the two-photon Dicke model

Abstract: The Dicke model is a paradigmatic quantum-optical model describing the interaction of a collection of two-level systems with a single bosonic mode. Effective implementations of this model made it possible to observe the emergence of superradiance, i.e., cooperative phenomena arising from the collective nature of light-matter interactions. Via reservoir engineering and analogue quantum simulation techniques, current experimental platforms allow us not only to implement the Dicke model but also to design more ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 88 publications
0
23
0
Order By: Relevance
“…In addition, recent theoretical proposals have shown that it is possible to engineer, in both trapped ions [ 44 ] and flux qubit systems [ 45 ], the suppression of the conventional dipole coupling, linear in the quantum field radiation, in order to access the peculiar phenomenologies, such as super-radiance and spectral collapse, which are associated to the two-photon coupling (quadratic in the radiation field) [ 46 , 47 , 48 , 49 , 50 , 51 ]. These ideas have also recently been considered in the context of QBs by some of us, showing that two-photon coupling, once realized, can lead to an even greater (proportional to M instead of ) enhancement of the averaged charging power [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent theoretical proposals have shown that it is possible to engineer, in both trapped ions [ 44 ] and flux qubit systems [ 45 ], the suppression of the conventional dipole coupling, linear in the quantum field radiation, in order to access the peculiar phenomenologies, such as super-radiance and spectral collapse, which are associated to the two-photon coupling (quadratic in the radiation field) [ 46 , 47 , 48 , 49 , 50 , 51 ]. These ideas have also recently been considered in the context of QBs by some of us, showing that two-photon coupling, once realized, can lead to an even greater (proportional to M instead of ) enhancement of the averaged charging power [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent theoretical proposals have shown that it is possible to engineer, in both trapped ions [44] and flux qubit systems [45], the suppression of the conventional dipole coupling, linear in the quantum field radiation, in order to access the peculiar phenomenologies, such as super-radiance and spectral collapse, which are associated to the two-photon coupling (quadratic in the radiation field) [46][47][48][49][50][51]. These ideas have also recently been considered in the context of QBs by some of us, showing that two-photon coupling, once realized, can lead to an even greater (proportional to M instead of √ M) enhancement of the averaged charging power [52].…”
Section: Introductionmentioning
confidence: 99%
“…Some recent proposals, based on trapped ions [50] or superconducting flux qubits [51] have suggested the possibility to suppress the dipole contribution, linear in the photon coupling, and to enhance the two-photon coupling. This configuration is predicted to lead to new and interesting physics, enhancing the visibility of a superradiant phase transition and hinting at a spectral collapse at high coupling [52][53][54][55][56][57].…”
Section: Introductionmentioning
confidence: 99%